PEMETAAN KARAKTERISTIK KIMIA BIJI KOPI ARABIKA GAYO DAN ROBUSTA GAYO - Maya Saputri; Hanifah Nuryani Lioe; C. Hanny Wijaya (Jurnal Teknologi dan Industri Pangan, 2020)
The distinctive aroma and taste of roasted coffee can be due to varietal differences in green coffee beans. The purpose of this research was to map the chemical characteristics of green coffee beans of Gayo arabica and Gayo robusta using principal component analysis (PCA) approach. Other analyses include pH using pH meter, total fats by Soxhlet method, total ash by gravimetric method, total protein by Kjeldahl method, total carbohydrates by difference, total soluble solids (TSS) by refractometer, organic acids composition by HPLC-UV/Vis, and total amino acids composition by UHPLC-PDAD. Six green coffee bean samples of Gayo arabica and Gayo robusta from different locations in Gayo, Aceh, as well as samples of arabica and robusta coffee beans each from plantation in West Java, Central Java and East Java (as comparators) were used in this study. The results showed the chemical characteristics of Gayo arabica and Gayo robusta could be mapped by PCA based on the concentrations of fats, organic acids and carbohydrates. The organic acid composition of Gayo arabica was associated with malic acid, succinic acid and citric acid, while Gayo robusta to acetic acid. The organic acids as well as TSS of the coffee beans could map Gayo arabica separately from Java arabica. Gayo arabica had higher organic acids, whereas Java arabica had higher TSS. Gayo robusta were characterized by higher fats, ash and total amino acids, but lower TSS than Java robusta. This study suggested the distinct characteristics of Gayo coffee beans to their corresponding coffee beans from Java.